CHARACTERIZATION OF A GENE THAT IS EXPRESSED IN LEAVES AT HIGHER LEVELS UPON TUBERIZATION IN POTATO AND UPON FLOWERING IN TOBACCO - Sonnewald, Uwe; et al. (Planta, 1993)
A partial cDNA clone has been isolated which represents a gene that is induced in potato (Solanum tuberosum L.) leaves upon tuber initiation. The gene is also present in tobacco (Nicotiana tobacum L.) where it is induced upon flowering, and in tomato (Lycopericon esculentum, L.) where it is induced when the plant starts to form fruit. This provides further evidence for the similarity of the floral-induction and tuber-induction pathways, and raises the possibility that this gene may be involved in a common step in both of these pathways. Alternatively, it could be involved in a secondary process that is induced during tuberisation, flowering and fruit development.
Keywords: FLORAL INDUCTION; LYCOPERSICON; NICOTIANA; SOLANUM; TUBERIZATION